(untitled) (Ibrahim Medical College Journal, 2014)
Dengue is an arboviral disease endemic in many parts of the world. The clinical presentation of dengue viral infection ranges from asymptomatic illness to fatal dengue shock syndrome. Although, it is known to cause hepatic involvement, it occasionally results in acute hepatic failure. We report a case of dengue hemorrhagic fever presenting with acute liver failure. The case recovered completely after treatment. DOI: http://dx.doi.org/10.3329/imcj.v7i2.20112 Ibrahim Med. Coll. J. 2013; 7(2): 41-42